Problem-Posing Activities in Primary School Mathematics Textbooks in Russia and Azerbaijan - Yasemin Deringöl; Elvira Guseinova (Universitas Pendidikan Indonesia, 2022)
Textbooks are one of the learning mediums. The activities in mathematics textbooks and qualities of these activities are of paramount importance. Problem-posing is one of the activities in these textbooks. Many researchers emphasize that examination of textbooks is important in explaining student success. The purpose of this study was to examine the problem-posing activities in the primary school mathematics textbooks in Russia and Azerbaijan. To this end, these textbooks were analysed and compared by content analysis according to the aforementioned countries and years. It was found out that there were more problem-posing activities in Russian textbooks than Azerbaijani textbooks in terms of both number and variety. In addition, it is considered that the number of problem-posing activities in textbooks should be increased and these problem-posing activities should be diversified.